DisCoTune: versatile auxiliary plasmids for the production of disulphide‐containing proteins and peptides in the E. coli T7 system. Issue 6 (18th August 2021) - Bertelsen, Andreas B.; Hackney, Celeste Menuet; Bayer, Carolyn N.; Kjelgaard, Lau D.; Rennig, Maja; Christensen, Brian; Sørensen, Esben Skipper; Safavi‐Hemami, Helena; Wulff, Tune; Ellgaard, Lars; Nørholm, Morten H. H.
Summary: Secreted proteins and peptides hold large potential both as therapeutics and as enzyme catalysts in biotechnology. The high stability of many secreted proteins helps maintain functional integrity in changing chemical environments and is a contributing factor to their commercial potential. Disulphide bonds constitute an important post‐translational modification that stabilizes many of these proteins and thus preserves the active state under chemically stressful conditions. Despite their importance, the discovery and applications within this group of proteins and peptides are limited by the availability of synthetic biology tools and heterologous production systems that allow for efficient formation of disulphide bonds. Here, we refine the design of two DisCoTune (Disulphide bond formation in E. coli with tunable expression) plasmids that enable the formation of disulphides in the highly popular Escherichia coli T7 protein production system. We show that this new system promotes significantly higher yield and activity of an industrial protease and a conotoxin, which belongs to a group of disulphide‐rich venom peptides from cone snails with strong potential as research tools and pharmacological agents. Abstract : Secreted proteins and peptides hold large potential both as therapeutics and as enzyme catalysts in biotechnology. Despite their importance, the discovery and applications within this group of proteins and peptides are limited by the availability of synthetic biology tools and heterologous production systems that allow for efficient formation of disulfide bonds. Here, we refine the design of two plasmids that enable the formation of disulfides in the highly popular Escherichia coli T7 protein production system.